A differentially amplified motion in the ear for near-threshold sound detection - Chen, Fangyi (2011)
The ear is a remarkably sensitive pressure fluctuation detector. In guinea pigs, behavioral measurements indicate a minimum detectable sound pressure of ~20 μPa at 16 kHz. Such faint sounds produce 0.1 nm basilar membrane displacements, a distance smaller than conformational transitions in ion channels. It seems that noise within the auditory system would swamp such tiny motions, making weak sounds imperceptible. Here, a new mechanism contributing to a resolution of this problem is proposed and validated through direct measurement. We hypothesize that vibration at the apical end of hair cells is enhanced compared to the commonly measured basilar membrane side. Using in vivo optical coherence tomography, we demonstrated that apical-side vibrations peak at a higher frequency, had different timing, and were enhanced compared to the basilar membrane. These effects depend nonlinearly on the stimulus level. The timing difference and enhancement are important for explaining how the noise problem is circumvented.